Could a loss of memory T cells limit responses to hepatitis C virus (HCV) antigens in blood leucocytes from patients chronically infected with HCV before and during pegylated interferon-a and ribavirin therapy? - Lee, S.; Hammond, T.; Watson, M.; Flexman, J.; Cheng, W.; Fernandez, S.; Price, Patricia (2010)
The proportions and activation status of T cells may influence responses to hepatitis C virus (HCV) and treatment outcome in patients receiving pegylated interferon (IFN)-a/ribavirin therapy. We confirmed that IFN-? enzyme-linked immunospot (ELISPOT) responses to HCV are poor in HCV patients and showed that responses to HCV and cytomegalovirus (CMV) antigens decrease during therapy. This was most apparent in patients with sustained virological response (SVR). Baseline frequencies of CD4+ effector memory (TEM) T cells were lower in SVR than non-SVR. Proportions of CD4+ and CD8+ TEM and terminally differentiated effector memory (TEMRA) T cells declined on therapy in SVR, as did proportions of Fas+ CD8+ TEMRA T cells. Baseline frequencies of programmed death (PD)-1-expressing CD4+ TEM and T EMRA T-cells were higher in SVR. Therapy increased percentages of PD-1+ CD4+ central memory (TCM) T cells and PD-1+ CD8+ TEM and TEMRA T cells in SVR. We conclude that successful therapy depletes circulating antigen-specific CD4+ T cell responses. This paralleled decreases in proportions of effector memory T cells and higher percentages of CD4+ TCM T cells expressing PD-1. © 2010 British Society for Immunology.